Thioredoxins m regulate plastid glucose-6-phosphate dehydrogenase activity in Arabidopsis roots under salt stress - Née, Guillaume; Wang, Fuzheng; Châtel-Innocenti, Gilles; Mhamdi, Amna; Juranville, Eugénie; Vanacker, Hélène; Noctor, Graham; Issakidis-Bourguet, Emmanuelle (Frontiers in Plant Science, 2023)
Plants contain several NADPH-producing enzymes including glucose-6-phosphate dehydrogenases (G6PDH) with different sub-cellular localizations. The activity of plastidial G6PDHs is redox-regulated by thioredoxins (TRX). Although specific TRXs are known to regulate chloroplastic isoforms of G6PDH, little information is available for plastidic isoforms found in heterotrophic organs or tissues. Here, we investigated TRX regulation of the two G6PDH plastidic isoforms of Arabidopsis roots during exposure to a mild salt stress. We report that in vitro m-type TRXs are the most efficient regulators of the G6PDH2 and G6PDH3 mainly found in Arabidopsis roots. While expression of the corresponding G6PD and plastidic TRX genes was marginally affected by salt, it impaired root growth of several of the corresponding mutant lines. Using an in situ assay for G6PDH, G6PDH2 was found to be the major contributor to salt-induced increases in activity, while data from ROS assays further provide in vivo evidence that TRX m acts in redox regulation during salt stress. Taken together, our data suggest that regulation of plastid G6PDH activity by TRX m may be an important player regulating NADPH production in Arabidopsis roots undergoing salt stress.